COMPARATIVE ANTIMICROBIAL EFFICACY OF LAVENDER AND MINT ESSENTIAL OILS: A PROMISING ALTERNATIVE FOR VETERINARY APPLICATIONS - Abdulkarim, Renas Ihsan; Issa, Nawzat Aboziad (Science Journal of University of Zakho, 2025)
With the increasing prevalence of antimicrobial resistance (AMR) in veterinary pathogens, there is a growing need to explore alternative therapeutic options. This study presents a direct comparative analysis of the antimicrobial efficacy of mint and lavender essential oils (EOs) against key veterinary pathogens, including Escherichia coli, Pasteurella multocida, Proteus mirabilis, Klebsiella pneumoniae, Corynebacterium pseudotuberculosis, Streptococcus agalactiae, and methicillin-resistant Staphylococcus aureus (MRSA). Antimicrobial potency was investigated through the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), along with conducting time-kill assays and antibiotic interaction studies using disc diffusion and broth dilution methods. While both essential oils have potential as alternative antimicrobial agents, lavender EO stands out, especially against drug-resistant bacteria like MRSA. Lavender EO was more bactericidal, killing most isolates within four hours, whereas mint EO needed a full 24 hours for its full efficacy. MICs ranged between 12 and 40 µL/mL, with slightly lower MICs with lavender against K. pneumoniae. Noticeably, Lavender EO demonstrated a strong synergistic effect with antibiotics, particularly enhancing the efficacy of penicillin and tetracycline against MRSA. In contrast, mint EO exhibited only limited synergy and, at times, an antagonistic interaction. These findings highlight the superior antimicrobial potential of lavender EO over mint EO, underscoring its therapeutic value in veterinary medicine